2004
DOI: 10.1074/jbc.m407171200
|View full text |Cite
|
Sign up to set email alerts
|

Human Pax-5 C-terminal Isoforms Possess Distinct Transactivation Properties and Are Differentially Modulated in Normal and Malignant B Cells

Abstract: The transcription factor Pax-5 occupies a central role in B cell differentiation and has been implicated in the development of B cell lymphoma. The transcriptional activation function of Pax-5 requires an intact N-terminal DNA-binding domain and is strongly influenced by the C-terminal transactivation domain. We report the identification and characterization of five human Pax-5 isoforms, which occur through the alternative splicing of exons that encode for the C-terminal transactivation domain. These isoforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 49 publications
2
61
1
2
Order By: Relevance
“…Developmentally, PAX5 can inhibit apoptosis (24). Recently, a number of alternate isoforms of PAX5 resulting from differential splicing have been described, although the relative oncogenic and developmental importance of these different forms has not been well characterized (25). Taken together, these findings suggest that PAX5 is likely to play a critical role in tumor maintenance.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Developmentally, PAX5 can inhibit apoptosis (24). Recently, a number of alternate isoforms of PAX5 resulting from differential splicing have been described, although the relative oncogenic and developmental importance of these different forms has not been well characterized (25). Taken together, these findings suggest that PAX5 is likely to play a critical role in tumor maintenance.…”
Section: Introductionsupporting
confidence: 51%
“…We measured PAX5 expression in a panel of adult tissues and cancer cell lines to confirm its limited tissue expression in normal tissues and its relative up-regulation in malignancy. We used quantitative reverse transcription-PCR (RT-PCR) using primers amplifying exon 8, which is thought to be present in most, but not all, splice variants (25). We also chose exon 8 because it encodes the epitope TLPGYPPHV, which was subsequently chosen for targeted immune response generation (see below).…”
Section: Resultsmentioning
confidence: 99%
“…However, incubation of the B-cell line RAJI at RT for 24 or 48 h induced the expression of PAX5 isoforms and subsequent re-cultivation at 37°C reversed this process (Fig 1E), supporting the hypothesis of cold shock-stimulated illegitimate splicing. These data corroborate the recent finding that FL-PAX5 is always the predominant isoform (Arseneau et al, 2009), but contradict earlier studies in which PAX5 variants, rather than FL-PAX5, were expressed in some B-cell lines (Robichaud et al, 2004;Arseneau et al, 2009).Cloning and sequencing of a number of splice variants amplified from 'aged' normal lymphocytes revealed that all isoforms identified corresponded to those previously described (Borson et al, 2002;Robichaud et al, 2004;Arseneau et al, 2009), including transcripts with various deletions of exons such as D2, D7/8, D2/7/8, D2/7/8/9, D2/4/8, and D2/3/4/8. Importantly, also the PAX5D2 isoform, which has been recently suggested to play a role in the development of BCP-ALL (Santoro et al, 2009), was readily expressed in 'aged' normal lymphocytes.…”
supporting
confidence: 46%
“…Disturbingly, the PAX5 isoform expression patterns observed were inconsistent between studies, even in normal B-cells. Thus, it has been questioned whether these variations result from an irreproducible pattern of PAX5 alternative transcripts or distinct expression patterns that are associated with specific B-cell malignancies (Borson et al, 2002;Robichaud et al, 2004;Sadakane et al, 2007;Sekine et al, 2007). While a recent study did not reveal any significant differences in the PAX5 transcript patterns between normal and cancerous B-lymphocytes derived from chronic lymphocytic leukaemia and lymphoma (Arseneau et al, 2009), others claim that either a higher number or even leukaemia-specific isoforms are expressed in B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) (Santoro et al, 2009).…”
mentioning
confidence: 99%
“…This generates transcripts with distinct first exons, 1A and 1B, with otherwise identical inframe sequences. Moreover, alternative splicing events throughout the transcript generate multiple protein isoforms (7). However, due to the inherent challenges of isoform variant analysis, not much is known about the contribution of the Pax-5 variant proteins in normal and cancerous contexts.…”
Section: Role Of Pax-5 In Developmentmentioning
confidence: 99%